Callus Induction from the Leaves and Organogenesis from the Leaf induced Calli of Piper longum L. - Wasti, Anupa; Pant, Krishna Kumar (International Journal of Bio-resource and Stress Management, 2019)
The aim of this research was the production and organogenesis of callus from leaf explants of Piper longum L. an important medicinal plant. The mother stocks were collected from the natural habitats at Ratnanagar, Chitwan and were cultivated at the central department of botany for experimental use. The basal medium used for all the experiments was Murashige and Skoog’s medium and the standard sterilization, inoculation and incubation procedures were applied. The young leaves were cultured in vitro on different concentration of 2,4-D (0.5-5.0 mg l-1) for callus induction. Among them, 3.0-4.0 mg l-1 2,4-D gave hard and compact yellow colored callus. These 2,4-D mediated calli were transferred to thirty different media (BAP, NAA, Kinetin, coconut water) for organogenesis. Most of the media did not show any response but some of them responded well. For shoot bud induction from callus, 0.5 mg l-1 Kn and 0.1 mg l-1 BAP responded but 0.1 mg l-1 BAP was found to be the best with 5±0.73 shoot buds per culture (highly significant). Root induction on 0.1 mg l-1 Kn, 1.0 mg l-1 BAP+0.1 mg l-1 NAA and 2.0 mg l-1 BAP+0.1 mg l-1 NAA were highly significant among all the media tested. Maximum number of roots (12±1.21 roots per culture) was recorded from the MS medium containing 1.0 mg l-1 BAP+0.1 mg l-1 NAA.